2008
DOI: 10.1590/s1517-83822008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the trehalose levels on the screening of yeast as probiotic by in vivo and in vitro assays

Abstract: Probiotics are viable defined microorganisms (bacteria or yeasts) that exert a beneficial effect on the health of the host when ingested in adequate amounts. Screening for such biotherapeutic agents is commonly performed by in vitro assays simulating gastrointestinal environment to determine the ability to survive in the digestive tract. In the present study, the possibility of extrapolation of data obtained in in vitro assays to in vivo conditions was studied using five Saccharomyces cerevisiae strains isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The UFMG20 and UFMG24 strains were selected from a yeast collection based on their high tolerance to mild heat shock and high trehalose accumulation following stress treatments (Martins et al , 2008). The rationale underlying this selection was that strains isolated from nature are usually more resistant to stress and that trehalose accumulation is generally used as an general indicator of stress resistance (Voit, 2003; Martins et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UFMG20 and UFMG24 strains were selected from a yeast collection based on their high tolerance to mild heat shock and high trehalose accumulation following stress treatments (Martins et al , 2008). The rationale underlying this selection was that strains isolated from nature are usually more resistant to stress and that trehalose accumulation is generally used as an general indicator of stress resistance (Voit, 2003; Martins et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Saccharomyces boulardii tolerance to a simulated gastric environment (an aqueous solution containing 86 mM NaCl, 3 g L −1 pepsin at pH 2.0) was determined by measuring yeast viability over time in comparison to S. cerevisiae wild‐type strains W303 (a laboratory strain), UFMG20 and UFMG24. The UFMG20 and UFMG24 strains were selected from a yeast collection based on their high tolerance to mild heat shock and high trehalose accumulation following stress treatments (Martins et al , 2008). The rationale underlying this selection was that strains isolated from nature are usually more resistant to stress and that trehalose accumulation is generally used as an general indicator of stress resistance (Voit, 2003; Martins et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A probiotic strain must be tolerant to various stresses, such as low pH and a high concentration of bile in the intestine [ 13 ]. Different bacterial species have different degrees of tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…From 103 initial strains, we based our first screening on the capacity of the strains to grow at 37°C. The following selection steps using experiments with animal models were important, since in a previous work we have observed that growth or survival of yeast strains to in vitro conditions mimicking the harsh environment of the gastrointestinal tract (low pH, gastric secretions, bile) are sometimes difficult to extrapolate to an in vivo situation (Martins et al 2008). In conclusion, P. kluyveri strain 898 showed to be the best candidate for probiotic use among the 103 yeast tested, as demonstrated by the following properties: thermotolerance, colonization and survival in the digestive tract without pathogenic effects, ability of in vivo antagonism against enteropathogenic bacterium and protective effect in animals during experimental infection.…”
Section: Resultsmentioning
confidence: 99%
“…However, some authors have suggested the use of other yeast species or genera based essentially on in vitro assays and very few clinical trials (Kovacs and Berk 2000;Kumura et al 2004; Van der Aa Kühle et al 2005;Martins et al 2008). Genetically, S. boulardii is nearly identical to S. cerevisiae, but very different metabolically (Fietto et al 2004).…”
Section: Introductionmentioning
confidence: 99%